Sensory-motor perception and neuromuscular coordination and their relationship to weight-throwing skill - Zahraa jaffar husein; Sajjad kareem ghunaim (Global Scientific Publishing, 2024)
Performing the skill of pushing a weight requires the availability of a set of requirements that overlap, such as physical structure, physical and mental skills, correct performance of basic skills, and other requirements. Sensory-motor perception and neuromuscular coordination stand out as one of these requirements that specialists emphasise. Through the need for many games for physical and mental abilities to reach artistic performance to the highest level, the researchers decided to study this problem by finding the relationship between sensory-motor perception and neuromuscular coordination in the skill of throwing weights. Performing sports movements requires a degree of compatibility between the nervous and muscular systems and sensory-motor perception. The importance of sensory-motor perception and its relationship to neuromuscular compatibility in the skill of throwing a weight is highlighted through the player’s ability to organize motor actions in the basic skills of the game, including the skills of holding and carrying the weight. The pushing mode and the pushing movement and its follow-up, and that kinaesthetic perception has a significant role in the players’ performance through the player’s motivation and desire to engage in sporting activity, and that the link between neuromuscular compatibility and kinaesthetic perception leads to the player’s success in accurately performing the skill well and their impact on Different training and competition conditions. The descriptive method was used with its survey study to suit the nature of this research. The sample was chosen from the original community, which consisted of (30) female students from the second stage. The sample became (20) female students, constituting (79.65%) of the original community. The female students included in the exploratory experiment, who numbered (10) female students, were randomly selected. From the indigenous community, where they constitute (20.35%). The research aims to - identify sensory-motor perception and neuromuscular coordination and its relationship to the skill of throwing weights. And identifying the degree of relationship between sensory-motor perception and neuromuscular coordination and its relationship to the skill of throwing weights.
Keywords: descriptive; relationship; experiment; throwing